Coherent normalization for in vivo measurements of gadolinium in bone. (21st September 2017) - Keldani, Z; Lord, M L; McNeill, F E; Chettle, D R; Gräfe, J L
Abstract: Objective : Recent evidence of gadolinium (Gd) deposition in bones of healthy individuals who have previously received Gd-based contrast agents (GBCAs) for MRI has led to a demand for in vivo measurement techniques. The technique of x-ray fluorescence provides a low risk and painless method to assess Gd deposition in bone, and has the potential to be a useful clinical tool. However, interpatient variability creates a challenge while performing in vivo measurements. Approach : We explored the use of coherent normalization, which involves normalizing the Gd K x-rays to the coherent scattered γ -ray from the excitation source, for bone Gd measurements through a series of phantom-based experiments and Monte Carlo simulations. Main results : We found coherent normalization is able to correct for variation in overlying tissue thickness over a wide range (0–12.2 mm). The Gd signal to coherent signal ratio is independent of tissue thickness for both experiments and Monte Carlo simulations. Significance : Coherent normalization has been demonstrated to be used in practice with normal healthy adults to improve in vivo bone Gd measurements.